Analysis of User Content Retrieval Delay Based on the Matern Hard-Core Point Process of Type II. (4th September 2018) - Zhao, Shuyuan; Zhao, Jihong; Qu, Hua; Ren, Gongye
Abstract : The content retrieval delay is an important performance metric for enhancing user experience in wireless networks. In this paper, by modeling the locations of the base stations (BSs) as the Matern hard-core point process of type II (MHP), we analyze the content retrieval delay for a typical cache-enabled device in wireless networks under the most popular content policy. Since it is intractable to get the size distribution of a Voronoi cell in the MHP model, we propose an approximate formula based on the empirical result in the Poisson point process and derive the cellular load which denotes the number of the user devices connected to a randomly chosen BS. Since the probability generating functional for MHP does not exist, we also propose approximate methods for the coverage probability of the MHP model. At last, we derive the cumulative distribution function of the content retrieval delay. Simulation results validate the accuracy of our analytical conclusions for user content retrieval delay.